Dynamical Demixing of a Binary Mixture Under Sedimentation (Communications in Computational Physics, 2023)
We investigate the sedimentation dynamics of a binary mixture, the speciesof which differ by their Stokes coefficients but are identical otherwise. We analyzethe sedimentation dynamics and the morphology of the final deposits using Browniandynamics simulations for mixtures with a range of sedimentation velocities of bothspecies. In addition, we use the lattice Boltzmann method to study hydrodynamiceffects. We found a threshold in the difference of the sedimentation velocities abovewhich the species in the final deposit are segregated. The degree of segregation increases with the difference in the Stokes coefficients or the sedimentation velocitiesabove the threshold. We propose a simple analytical model that captures the mainfeatures of the simulated deposits.